The Impact of Transmission and Distribution Price Reform on Economic Growth in Liberalized Electricity Markets: An Inter-Provincial Panel Data Analysis - Li, Hong; Wang, Xiaogang; Xie, Yuantao; Chen, Ting; Han, Haoming; Yang, Yichen (Frontiers in Environmental Science, 2022)
This paper investigates and quantifies the extent of the Transmission and Distribution Price Reform (TDPR) on economic growth. Provincial-level data from 2010 to 2019 was used to estimate the impacts of the TDPR on economic growth using a progressive difference in differences method (DID). Findings showed that the reform had a positive impact on regional GDP and regional GDP per capita. Furthermore, to explore its mechanism of influence, the impacts of the TDPR on electricity prices, including the average sale prices and sale prices for industrial users, were analyzed, and the evidence suggests that the TDPR has significantly reduced the sale price. Additionally, the regression result suggests that the TDPR mainly affects electricity prices to reduce the energy cost of enterprises, and then promotes the innovation of industrial enterprises above designated size (IEADS) and fixed asset investment, which act on total factor productivity and promote regional economic growth. The regression results showed good robustness under various robustness tests.